Expanding Posttraumatic Growth: An Examination of Male Survivors of Sexual Violence - Cima, Samantha (Université d'Ottawa / University of Ottawa, 2019)
Societal discourses and rigid gender norms, tenaciously reinforced by media representations, prevent men from being recognized as survivors of sexual violence (Gulas, McKeage, & Weinberger, 2010; Heber, 2017). Consequently, research on the ability of male survivors of sexual violence to acquire positive characteristics as a result of their victimization, termed posttraumatic growth (PTG), is limited (Tedeschi & Calhoun, 2004a). This thesis assesses the experience of PTG for male survivors of sexual violence, specifically analyzing the role of gender norms, coping styles, and service access in the production, or lack thereof, of PTG. Through the concepts of gender norms and coping, the experience of PTG for male survivors is contextualized, providing insight into how these forces individually and collectively facilitate or hinder the experience of PTG. A qualitative comparative analysis is conducted in order to establish a configuration of causal factors that are associated with the presence and absence of PTG for male survivors (N=9). Only one of the five hypotheses this thesis tests are supported; high stability (no interruption) of service access is associated with PTG. This thesis argues that the use of coping styles and service access is intertwined with conflicts between their gender and victimization, where male survivors utilize certain forms of coping or services depending on the degree to which they need to regain feelings of control.
Keywords: posttraumatic growth; male survivors; sexual violence; gender norms; coping; service access